Crocodyliformes and Testudines from the Eocene of the Duero Basin (northwestern Spain): an update of their diversity and stratigraphic context. (3rd August 2022) - Ortega, Francisco; Armenteros, Ildefonso; de Celis, Ane; Escaso, Fernando; Huerta, Pedro; Martín de Jesús, Santiago; Narváez, Iván; Pérez-García, Adán; Sanz, José Luis
ABSTRACT: The Palaeogene sedimentary successions of the Duero Basin host an important record of fossil vertebrates, especially mammals and reptiles. The main fossil sites are placed at the west margin (Salamanca and Zamora areas) spanning from the Lutetian to the late Priabonian; and at the southeast tip (Almazán Basin) mainly Bartonian in age. The continued study of the sites is supplying new data that will improve the chronostratigraphy and the correlation between the western and eastern regions of the basin. The diversity and phylogenetic relationships of the represented fauna have been revised in recent years with the reassignment of some remains and the diagnosis of some new taxa. Four lineages of turtles are represented: Podocnemididae ( Neochelys ), Carettochelyidae ( Allaeochelys ), Trionychidae and Testudinidae ( Pelorochelon ). Crocodyliform paleobiodiversity is composed of notosuchians (close to Iberosuchus ) and, at least, three crocodylian lineages: Planocraniidae ( Duerosuchus ), Alligatoroidea ( Diplocynodon ) and Crocodyloidea (' Asiatosuchus '). The distribution of these taxa is not homogeneous throughout the basin, and a deep transformation is recognised throughout the middle Eocene. The fitting of the distribution and relationships of the reptilian fauna from the Duero Basin provides valuable information to understand some faunistic dynamics such as the endemism process of northwestern Iberia from the middle of the Eocene.